Early management of the Acute Closed Lock of the Temporomandibular Joint - Yusuf Emes; Buket Aybar (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2017)
Disc displacement without reduction (DDwoR), which is common among the temporomandibular disorders (TMD's) may be diffi cult to deal with by the clinician. The term closed lock usually refers to the condition of DDwoR and manifest itself with painful limited mouth opening [1], and may sometimes be diffi cult to differentiate from other clinical entities such as spasm of the lateral pterygoid muscle or anchored disc phenomenon [2], It is generally considered that intervening in the early stages of the closed lock leads to a better prognosis. However, the term acute closed lock is still a matter of debate. Closed lock lasting less than one week is generally considered to be acute [3], but some researchers have extended this period up to 4 weeks [4]. Two thirds of the patients with closed lock tend to improve over time. However, this means that one third of them don't or even worsen over time [2], therefore, that the clinician has to attempt to correct this disorder as soon as possible.